“THE EFFECT OF PROMOTION AND PERCEPTION OF THE QUALITY OF ADVAN SMARTPHONE PRODUCTS ON PURCHASE INTEREST IN THE DUKOMSEL STORE BANDUNG” - Suganda, Uce Karna (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to determine the effect of promotion and perceived quality of ADVAN smartphone products on Purchase Interest in prospective Dukomsel Store Bandung consumers. The factors tested in this study were promotion and product quality perception as an independent variable. While Purchase Interest as the dependent variable. The research method used in this research is descriptive and verification methods. The population in this study are people who are interested in buying ADVAN smartphones in the Dukomsel Bandung Store. The sampling technique used in this study is non-probability sampling using a purposive sampling technique with a sample size of 170 respondents. While the analytical method used in this study is multiple linear regression analysis and the coefficient of determination at a significant level of 5%. The program used in analyzing data uses Statistical Package for Social Sciences Ver. 24.00 The results showed that the promotion of ADVAN Smartphones had a positive and significant effect on Purchase Interest, the better the promotion carried out would increase Purchase Interest. The results showed that the perception of the quality of ADVAN Smartphone products had a positive and significant effect on Purchase Interest, the better the perception of product quality would increase Purchase Interest. Promotion and perception of product quality has an influence on Purchase Interest of 43.3%, while the remaining 56.7% is contributed by other variables not examined.